Activities aimed at encouraging children to suicidal behavior: judicial-psychological examination - Safuanov F.S.; Sekerazh T.N. (Психология и право, 2017)
Federal law of June 7, 2017 g. № 120-FZ "On amendments to the criminal code of the Russian Federation and article 151 of the Criminal procedure code of the Russian Federation in the part of establishing additional mechanisms to counter activities aimed at encouraging children to suicidal behavior" establishes criminal liability for inducement to commit suicide or assist in its Commission (article 110.1 of the criminal code), as well as for the organization of activities aimed at encouraging citizens to commit suicide (article 110.2 of the criminal code). Two additions to the criminal code include using a publicly performed work, the media or information and telecommunications networks (including network "Internet"). There are new legal consequences relevant to forensic psychological assessment related to suicide. The article analyzes the legal situation (pre-investigation check of materials and incitement to suicide) that define the subject of judicial-psychological or psychological and psychiatric examinations as the mental state of the subject in the period preceding the suicide (death). Legislative innovations require expertise in psychology and linguistics. One of the subjects of psychological-linguistic expertise is the focus of the information material (text, graphic, together verbal and non-verbal information) or the communicative activity of the subject to encourage the addressee to co-concluding suicide. Formulate possible questions for the ex-experts and psychologists.